2011
DOI: 10.1126/scisignal.2002208
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Driven Maturation and Plasma Membrane Insertion of Calcium-Sensing Receptors Dynamically Control Signal Amplitude

Abstract: Calcium-sensing receptors (CaSRs) regulate systemic calcium homeostasis in the parathyroid gland, kidney, intestine, and bone and translate fluctuations in serum calcium into peptide hormone secretion, cell signaling, and regulation of gene expression. The CaSR is a G protein (heterotrimeric guanosine triphosphate-binding protein)-coupled receptor that operates in the constant presence of agonist, sensing small changes with high cooperativity and minimal functional desensitization. Here, we used multiwavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 51 publications
5
99
0
2
Order By: Relevance
“…Constitutive internalization of CaSR has been observed in some studies (52,53), and moreover, a distinct regulatory mechanism for CaSR has been reported in which agonist stimulation triggers further insertion of receptors in the cell membrane from intracellular stores, thereby increasing the amount of receptors available for activation. This mechanism has been named agonist-driven insertional signaling (54). Finally, the ā„-aminobutyric acid B (GABA B ) receptors do not internalize in response to agonist; however, they do exhibit constitutive internalization and subsequent recycling (55)(56)(57) in line with our current observations for the GPRC6A receptor.…”
Section: Discussionsupporting
confidence: 84%
“…Constitutive internalization of CaSR has been observed in some studies (52,53), and moreover, a distinct regulatory mechanism for CaSR has been reported in which agonist stimulation triggers further insertion of receptors in the cell membrane from intracellular stores, thereby increasing the amount of receptors available for activation. This mechanism has been named agonist-driven insertional signaling (54). Finally, the ā„-aminobutyric acid B (GABA B ) receptors do not internalize in response to agonist; however, they do exhibit constitutive internalization and subsequent recycling (55)(56)(57) in line with our current observations for the GPRC6A receptor.…”
Section: Discussionsupporting
confidence: 84%
“…NPS2143 will likely have a similar pharmacokinetic profile. Resetting at the level of receptor can involve regulation of its gene expression, protein trafficking, and endocytosis 34 or interaction with adaptor proteins, such as filamin A 35 and AP2S1. 36 The renal role of CaSR in calcium metabolism has been difficult to delineate owing to its effects on PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins interact with the CaSR when the receptor exits from the ER, including p24A (transmembrane emp24 domain trafficking protein 2(TMED2)) [101]; the small GTP-binding protein Sar1 [102]; receptor-activitymodifying proteins (RAMPs) [96]; Rab1 [103]; calmodulin (CaM) [63]; 14-3-3 [104] and Dorfin [90]. p24A binds predominantly to the immature form of the CaSR and cycles between the ER, the ER-Golgi intermediate compartment (ERGIC) and the cis-Golgi membranes [105,106].…”
Section: Trafficking Of the Casr In Cellsmentioning
confidence: 99%
“…Both of them are found to facilitate the CaSR trafficking from ER to Golgi [96,103]. The 14-3-3 protein is predicted to interact with the arginine-rich domain of the CaSR ( 890 RRxxxxRKR 898 ) and may lead to the retention of the CaSR in the ER [65,104,107]. There is also a calmodulin-binding site in the C-tail of the CaSR comprising residues 874ļ€­895 [47].…”
Section: Trafficking Of the Casr In Cellsmentioning
confidence: 99%
See 1 more Smart Citation